Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.joule.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Electric Strain in Dual Metal Janus Nanosheets Induces Structural Phase Transition for Efficient Hydrogen Evolution

Abstract: The future of sustainable energy supply demands innovative breakthroughs in the design of cheap and durable catalysts for efficient electrochemical water splitting. Distinct from the conventional doping, defecting, and nanostructuring strategy, we develop a simple and feasible electric-strain way to trigger electrocatalyst's structural phase transition via regulating carrier distribution, realizing an excellent hydrogen evolution reaction (HER) performance. Herein, thanks to the intrinsic noncentrosymmetric po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 31 publications
(29 reference statements)
0
42
0
Order By: Relevance
“…[ 29 ] Similarly, Fu et al prepared MoReS 3 with a layered structure, a new type of TMDs, and it showed excellent hydrogen evolution in electrocatalysis. [ 30 ] As a new type of TMDs, ReS 2 has been studied in photocatalytic hydrogen evolution (PHE), both experimentally and theoretically. [ 31–38 ] Zhang et al [ 34 ] reported that ReS 2 exhibited significant performance in PHE, a two‐electron catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] Similarly, Fu et al prepared MoReS 3 with a layered structure, a new type of TMDs, and it showed excellent hydrogen evolution in electrocatalysis. [ 30 ] As a new type of TMDs, ReS 2 has been studied in photocatalytic hydrogen evolution (PHE), both experimentally and theoretically. [ 31–38 ] Zhang et al [ 34 ] reported that ReS 2 exhibited significant performance in PHE, a two‐electron catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, regulating intrinsic electronic/phase structure seems the effective strategy for highly activity catalyst. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…2D heterostructures yield unusual properties and phenomena, benefiting from the synergistic properties of different 2D materials via high-quality heterointerfaces 15,16,23 . Strain engineering at the interfaces is an efficient approach to control the properties of 2D materials, which has been widely demonstrated in electronics and catalysis [24][25][26] . Only recently, an observation was reported that interface strain engineering of 2D carbon-MoS 2 heterostructured nanosheets could control the electrochemical reactivity of MoS 2 for Li insertion 27 .…”
mentioning
confidence: 99%